STRATEGI PEMASARAN DESTINASI WISATA KAMPUNG DURIAN DI KABUPATEN BENGKULU TENGAH - Armarani Septia Dwiputri; Budiman Sakti; Rahiman Dani (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2025)
This study aims to analyze the marketing strategy of Kampung Durian tourist destinations and identify the challenges faced in their implementation. The research uses a descriptive qualitative approach with data collection techniques through in-depth interviews, field observations, and documentation. The results of the study show that the marketing of Durian Village is quite successful in attracting tourists through the main attraction in the form of durian agrotourism, the involvement of local communities, and the beautiful rural natural atmosphere. However, marketing strategies still face obstacles in terms of limited infrastructure, low human resource capacity managers, lack of digital promotion, and low awareness of people outside the region. Therefore, it is necessary to improve services, strengthen destination branding, and integrate cross-sector promotion so that Durian Village can develop sustainably. Keywords: Tourism Marketing, Tourist Destinations, Durian Village